Evaluation of Patients Diagnosed with Brain Death in Paediatric Critical Care - Muhterem Duyu; Zeynep Karakaya (Galenos Yayinevi, 2020)
Aim:We aimed to investigate the rate of brain death (BD) determinations and organ donations in our tertiary pediatric intensive care unit (PICU), and to report the data on demographic pattern and supplementary descriptive data on the BD declarations.Materials and Methods:Age and gender of the cases were recorded, and also clinical conditions causing BD were grouped and recorded under six headings including; traumatic brain injury (TBI), brain neoplasm, cardiac arrest, intracranial haemorrhage, central nervous system infection and other causes. The time from the PICU admission to the diagnosis of BD, the time from suspicion of BD to final diagnosis, duration of survival after diagnosis of BD, confirmatory tests used, whether apnea test is performed, and inherent alterations (diabetes insipidus, hyperglycaemia, hypothermia) that occurred following diagnosis of BD were recorded. Organ donation rate, the name and number of organs harvested were determined.Results:Twenty-three patients were diagnosed with BD. The mean age of the patients diagnosed with BD was 5.5±4.9 years. The causative mechanism leading to BD was classified into six groups, out of which the most common diagnosis was TBI with a rate of 39.3%. The meantime from PICU admission to BD diagnosis was 5.7±5.5 days. The time period from suspicion of BD to the final diagnosis was 1.6±0.7 days and the meantime to develop cardiac arrest after diagnosis of BD was 13.1±21.6 days in non-donor cases. The most commonly used confirmation test was brain computed tomography angiography with 82.6%. The most common alteration that follow BD was diabetes insipidus (56.5%). Four patients became organ donors (17.4%).Conclusion:Patients with severe TBI are the most likely candidates for BD declaration and suitable for organ donation for children in need. Early diagnosis and good donor care are of great importance, especially for paediatric patients waiting for organ transplants.